Front Cover. Issue 10 (25th October 2019) - Fultz, Robert; Engevik, Melinda A.; Shi, Zhongcheng; Hall, Anne; Herrmann, Beatrice; Ganesh, Bhanu P.; Major, Angela; Haag, Anthony; Mori‐Akiyama, Yuko; Versalovic, James
Abstract : The cover image is based on the ORIGINAL ARTICLE Phagocytosis by macrophages depends on histamine H2 receptor signaling and scavenger receptor 1 by Robert Fultz et al., https://doi.org/10.1002/mbo3.908 . Cover image © Melinda Engevik Images